Pioneering spirit and village community of the future : Images of the future of church members of Jätkäsaari in the year 2040 - Oranen, Joel (My University, 2023)
This study focuses on images of the futures regarding community in Jätkäsaari in 2040. The data was gathered by organising a modified ACTVOD-workshop with cooperation of the local Evangelical-Lutheran parish. While invitation was open to all, all of the participants had ties to church and Jätkäsaari area. Jätkäsaari was selected as an area due to its rapidly developed nature, which may bring changes to the social fabric of the area. The main goal of this research is to map, what kinds of hopes and fears the participants have regarding the future of the area. This leads to the research question 1. What would good community look like in Jätkäsaari in 2040? ACTVOD-workshop was chosen as a research method due to its flexibility and yielding results in short amount of time. The workshop yielded data for the first research question, the second research question focuses on the workshop itself and how it could be developed. leading to research question 2. Is ACTVOD-workshop seen as a useful tool of creating future knowledge? The answer to this question is gathered with a survey questionnaire after the workshop. The results are analysed through inductive content analysis, using recordings of the discussions in the workshop as the primary material for analysis. This is enriched with physical notes and presentations produced in the workshop. The workshop was organised in Finnish. The content analysis resulted in four themes, which answer to the first research question. Themes are: Future of the Church, Security and Wellbeing, Virtual and Physical Community and Inclusivity and Services. Each theme focuses on different aspect that were found important in creating a good community in the future. Future of Church highlights the challenges faced by the church due lack of resources and dwindling number of church members and importance of church as a community for the participants. Security and Wellbeing dwells into rising lack of hope, identified in youth especially and recognises draining work life as one reason for reduced communal activity. Virtual and Physical Community focuses on discussions on new forms of communality and whether digitalisation is an avenue for more inclusive action, or a threat for physical communities. Inclusivity and Services emphasizes the importance of openness and acceptance for everybody. Different activities from hobbies to organising events within the community are seen as important communal actions. The survey answers provided answers to the second research question. The workshop was seen as a positive experience and an important forum for exchanging ideas about the future. Most criticized aspects were the constricted time ideation and difficulty of understanding instructions at times.

Tämä tutkimus keskittyy yhteisöä koskeviin tulevaisuuskuviin Jätkäsaaressa vuonna 2040. Aineisto kerättiin järjestämällä muokattu ACTVOD-työpaja yhteistoiminnassa paikallisen Evankelis-Luterilaisen seurakunnan kanssa. Vaikka kutsu työpajaan oli avoin kaikille, kaikilla osallistujilla oli yhteyksiä kirkkoon ja Jätkäsaaren alueeseen.Jätkäsaari valikoitui tarkasteltavaksi alueeksi sen nopean kehittämisen takia, mikä voi tuoda muutoksia alueen sosiaaliseen kudokseen. Tutkimuksen päätarkoituksena on kartoittaa, minkälaisia toiveita ja pelkoja paikallisilla on alueen tulevaisuutta kohtaan. Tämä johtaa tutkimuskysymykseen 1. Miltä hyvä yhteisö näyttää Jätkäsaaressa vuonna 2040? ACTVOD-työpaja valikoitui tutkimusmetodiksi sen joustavuuden ja sen lyhyessä ajassa tuottamien tulosten takia. Työpaja vastasi ensimmäiseen tutkimuskysymykseen, johtaen samalla tutkimuskysymykseen 2. Nähdäänkö ACTVOD-työpaja hyödyllisenä tapana luoda tulevaisuustietoa? Vastaus tähän kysymykseen kerättiin kyselyllä työpajan jälkeen. Tulokset analysoitiin induktiivisella sisällönanalyysilla käyttäen työpajassa käytyjen keskustelujen nauhoituksia ensisijaisena analyysin materiaalina. Aineistoa rikastettiin osallistujien luomilla fyysisillä muistiinpanoilla ja esityksillä. Työpaja järjestettiin suomeksi. Sisällönanalyysin lopputulokseksi saatiin neljä teemaa, jotka vastaavat ensimmäiseen tutkimuskysymykseen. The content analysis resulted in four themes, which answer to the first research question. Teemat ovat: Future of Church, Security and Wellbeing, Virtual and Physical Community and Inclusivity and Services. Jokainen teema keskittyy erilaiseen näkökulmaan, jotka koetaan hyvälle tulevaisuuden yhteisölle tärkeäksi. Future of Church korostaa kirkon kohtaamia haasteita johtuen resurssipulasta ja vähenevästä jäsenmäärästä, sekä kirkkoyhteisön tärkeydestä työpajaan osallistujille. Security and Wellbeing käsittelee kasvavaa toivottomuutta, erityisesti nuorten parissa. Teema tunnistaa myös kuluttavan työelämän yhdeksi vähentyneen yhteisöaktiivisuuden syistä. Virtual and Physical Community keskittyy keskusteluihin uusista yhteisöllisyyden muodoista ja siitä, onko digitalisaatio tie kohti inklusiivisempaa toimintaa vai uhka fyysisille yhteisöille. Inclusivity and Services korostaa avoimuuden ja kaikkien hyväksymisen tärkeyttä. Erilaiset aktiviteetit harrastuksista tapahtumien järjestämiseen nähdään tärkeänä yhteisöllisenä toimintana. Kyselyvastaukset vastaavat toiseen tutkimuskysymykseen. Työpaja koettiin positiivisena kokemuksena ja tärkeänä foorumina tulevaisuutta koskevien ideoiden vaihtamiseen. Kritisoiduimmat piirteet työpajassa olivat lyhyt ideointivaiheeseen omistettu aika sekä ajoittainen ohjeiden ymmärtämisen haasteellisuus.
Keywords: futures workshop, images of the future, community